A membrane electrode and its preparation method and application
After adding composite hydrophilic substances to the catalyst slurry of alkaline electrolytic membrane electrodes and removing them, the porosity and gas diffusion ability of the membrane electrodes are improved, and the existing membrane electrodes are solved, and the existing membrane electrodes are uneven coating and wide pore size distribution are achieved, thereby achieving high-efficiency and energy-saving electrolytic hydrogen production effect.
Patent Information
- Application Number
- CN202410243936.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-04
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-03-04
AI Technical Summary
The catalyst layer of the existing alkaline electrolytic membrane electrode has poor hydrophilicity, resulting in uneven coating, wide pore size distribution, low porosity, and affecting gas diffusion and ionic conductivity.
The coating uniformity of the slurry is improved by adding composite hydrophilic substances, including soluble hydrophilic substances, pore-forming non-hydrophilic substances and insoluble hydrophilic oxides to the catalyst slurry. These hydrophilic substances are then removed, the nanoscale pore size of the membrane electrode is increased, and the porosity and specific surface area are improved.
The coating uniformity of the membrane electrode and the qualification rate for the finished product are improved, the percentage of nano-scale pore size is increased, the ionic conductivity and gas diffusion capacity are improved, the chamber decomposition voltage and hydrogen production power are reduced, and the efficiency and energy saving effect is achieved.
Smart Images

Figure BDA0004725273700000091 
Figure BDA0004725273700000101 
Figure BDA0004725273700000102
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alkaline electrolyzed water preparation, and in particular to a membrane electrode and a preparation method and application thereof. Background Art
[0002] Alkaline water electrolysis is a relatively mature technology in the field of hydrogen production by water electrolysis. The membrane electrode assembly is the place where electrochemical reactions and multiphase material transfer take place, and is crucial to the energy consumption, life, and cost of hydrogen production devices by electrolysis. The membrane electrode used for water electrolysis generally has a sandwich-like structure, that is, a three-layer membrane electrode including a cathode / anode catalyst layer and a diaphragm, and can also be expanded to a five-layer or seven-layer membrane electrode including a cathode / anode gas diffusion layer and a sealing frame. High-performance membrane electrode preparation technology has always been the core technology in the field of hydrogen production by water electrolysis. In addition to obtaining the best electrolysis or power generation performance, it is also necessary to consider the durability of materials such as diaphragms, catalysts, gas diffusion layers, and practical engineering application issues such as gas cross-permeation. Therefore, the study of high-activity, low-cost, long-life membrane electrodes and their preparation processes is of great significance to accelerate the commercialization of diaphragm water electrolysis.
[0003] The integrated membrane electrode for alkaline water electrolysis adopts the form of CCM (catalyst coating membrane). The catalyst and binder in the catalyst layer of the membrane electrode currently prepared have poor hydrophilicity, wide pore size distribution and low porosity, and a hot pressing step is required in the preparation process. The hot pressing process further reduces the pore size and porosity. Too small pores are not conducive to gas diffusion, resulting in increased ionic conductivity of the membrane electrode.
[0004] In addition, the base membranes used in existing membrane electrodes are mostly fluoride membranes and polysulfone membranes with strong corrosion resistance. The metal catalyst slurry and organic base membranes used for alkaline water electrolysis are not hydrophilic, which makes the membrane coating uneven and the decomposition voltage of each chamber varies greatly. In the prior art, some base membranes increase the hydrophilicity of the base membrane by adding hydrophilic zirconium oxide particles, but the particles are unevenly distributed, and hydrophobic point holes still appear during the coating process, which cannot form a uniform membrane electrode with a large area. All of these have a great impact on the performance of the membrane electrode. Summary of the invention
[0005] In view of this, the main purpose of the present invention is to provide a membrane electrode and its preparation method and application, adding hydrophilic substances to the existing catalyst slurry to improve the coating uniformity of the slurry, and after removing these hydrophilic substances, increasing the nanoscale pore size of the membrane electrode, improving the porosity and narrowing the pore distribution range.
[0006] To achieve the above-mentioned object of the invention, the first aspect of the present invention provides a method for preparing a membrane electrode, comprising the following steps:
[0007] 1) mixing a catalyst, a binder and a composite hydrophilic substance to obtain a hydrophilic slurry, wherein the composite hydrophilic substance comprises one or more of a soluble hydrophilic substance, a pore-forming non-hydrophilic substance, and an insoluble hydrophilic oxide;
[0008] 2) coating the hydrophilic slurry on a substrate membrane to obtain a uniformly coated membrane electrode;
[0009] 3) drying and hot pressing the membrane electrode;
[0010] 4) Removing the soluble hydrophilic substances and / or pore-forming non-hydrophilic substances in the membrane electrode to obtain a porous hydrophilic membrane electrode.
[0011] Furthermore, in step 1), the soluble hydrophilic substance includes one or more of soluble organic matter and soluble salt.
[0012] Furthermore, in step 4), soluble organic matter is removed by placing the membrane electrode in an operating alkaline electrolysis stack, or by leaching the membrane electrode in alkaline solution or high-temperature alkaline solution or high-temperature water, or by placing the membrane electrode in an organic solvent or enzyme for degradation to remove soluble organic matter.
[0013] Furthermore, the soluble organic matter includes one or more of cellulose, alginic acid, starch, and gum arabic, and the molecular weight is preferably 10,000-1,000,000.
[0014] Furthermore, the soluble salt includes one or more of ammonium bicarbonate, ammonium carbonate, and sodium carbonate.
[0015] In some embodiments, a hydrophilic slurry containing a soluble salt is coated on a substrate membrane, and when the slurry is not dry, the soluble salt is decomposed by heating to release gas, thereby forming extremely small pores.
[0016] Furthermore, the pore-forming non-hydrophilic material includes one or more of silicon-based materials such as glass fiber or metals that can be dissolved by alkali solution.
[0017] In some embodiments, the pore-forming non-hydrophilic substance plays a place-occupying role in the prepared membrane electrode. In step 4), the pore-forming non-hydrophilic substance is removed by soaking or circulating the membrane electrode in a hot alkaline solution to form pores.
[0018] Furthermore, the insoluble hydrophilic oxide includes one or more of zirconium oxide, titanium oxide, molybdenum oxide and the like.
[0019] Furthermore, the added amount of the composite hydrophilic substance accounts for 0.1% to 20% of the total mass of the slurry.
[0020] Furthermore, in the composite hydrophilic substance, the mass ratio of the soluble hydrophilic substance, the pore-forming non-hydrophilic substance and the insoluble hydrophilic oxide is in the range of 0.1-10%: 0.1-5%: 0.1-5%.
[0021] Furthermore, the coating method in step 2) is spraying, blade coating, slit coating or screen printing;
[0022] Preferably, before the coating, the method further includes a pretreatment step of the base film: coating a mesh or dot-shaped hydrophilic organic layer on the surface of the base film; the hydrophilic organic material includes one or more of cellulose, alginic acid, starch, and gum arabic, and the molecular weight is preferably 10,000-1,000,000.
[0023] The second aspect of the present invention provides a membrane electrode prepared by the above method.
[0024] The third aspect of the present invention provides an application of a membrane electrode prepared by the above method, which is used for producing hydrogen by alkaline water electrolysis.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] Since the metal catalyst slurry and the base organic membrane for alkaline water electrolysis have poor hydrophilicity, the membrane coating is uneven and the decomposition voltage of each chamber varies greatly. The present invention can improve the hydrophilicity between the catalyst slurry and the base membrane by adding a composite hydrophilic substance that can be removed by leaching, heating or degradation, so that the surface tension of the slurry is reduced and the coating is easy to spread, thereby improving the uniformity of membrane electrode coating and improving the qualified rate of membrane electrode preparation products.
[0027] After coating the slurry containing the composite hydrophilic substance, the present invention removes part of the hydrophilic substance therein (occupying effect), such as soluble hydrophilic substance and pore-forming non-hydrophilic substance, thereby increasing the percentage of nanometer-level pore size, increasing the specific surface area, and improving the ionic conductivity. Practical application confirms that after SEM and specific surface area tests, the porosity is increased by 10% to 30% and the number of nanometer-level macropores that are easy for hydrogen and oxygen to diffuse increases. The remaining hydrophilic oxide is wrapped on the catalyst surface to provide water and ion sources for water electrolysis, thereby improving the catalyst utilization rate, and finally improving the electrode decomposition efficiency, reducing the small chamber decomposition voltage, reducing the hydrogen production power, and achieving high efficiency and energy saving effects.
[0028] Furthermore, before applying the hydrophilic slurry, a pretreatment step of the base membrane is also included: a mesh or dot-shaped hydrophilic organic layer is applied on the surface of the base membrane. This pretreatment method can make the composite hydrophilic slurry spread better on the base membrane, further improving the uniform coating degree of the membrane electrode.
[0029] Other features and advantages of the present invention will be described in detail through the following detailed description. DETAILED DESCRIPTION
[0030] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0031] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0032] Unless otherwise specified, the raw materials and reagents in the examples of the present invention can be purchased through commercial channels.
[0033] The first aspect of the present invention provides a method for preparing a membrane electrode, comprising the following steps:
[0034] 1) mixing a catalyst, a binder and a composite hydrophilic substance to obtain a hydrophilic slurry, wherein the composite hydrophilic substance comprises one or more of a soluble hydrophilic substance, a pore-forming non-hydrophilic substance, and an insoluble hydrophilic oxide;
[0035] 2) coating the hydrophilic slurry on a substrate membrane to obtain a uniformly coated membrane electrode;
[0036] 3) drying and hot pressing the membrane electrode;
[0037] 4) Removing the soluble hydrophilic substances and / or pore-forming non-hydrophilic substances in the membrane electrode to obtain a porous hydrophilic membrane electrode.
[0038] In some embodiments, in step 1), the soluble hydrophilic substance includes one or more of soluble organic matter and soluble salt.
[0039] In some embodiments, in step 4), soluble organic matter is removed by placing the membrane electrode in an operating alkaline electrolysis stack, or by leaching the membrane electrode in alkaline solution or high-temperature alkaline solution or high-temperature water, or by placing the membrane electrode in an organic solvent or enzyme for degradation to remove soluble organic matter.
[0040] Exemplarily, placing the membrane electrode in an alkaline electrolysis stack to remove soluble organic matter specifically includes: assembling the membrane electrode to the alkaline electrolysis stack, the removal conditions are heating the stack temperature to 30-100°C and circulating alkali solution or water; or circulating alkali solution with a concentration of 1% to 35% at room temperature alone; or circulating alkali solution with a concentration of 1% to 35% at 30-100°C; or circulating alkali solution with a concentration of 1% to 35% at 30-100°C and applying a certain current for electrolysis, and the alkali solution circulation time is 0.5h to 24h, and the soluble hydrophilic substances on the membrane electrode are removed under the above conditions. The mechanism is that the viscosity of aqueous organic matter decreases, decomposes, and falls off from the catalyst layer under alkaline conditions or high temperature alkaline conditions.
[0041] Exemplarily, removing soluble organic matter by leaching the membrane electrode in alkaline solution specifically includes: placing the membrane electrode in a 1% to 35% alkaline solution tank and stirring or ultrasonicating it, so that the hydrophilic organic matter is degraded into small molecules and leached under alkaline conditions.
[0042] Exemplarily, removing soluble organic matter by leaching the membrane electrode in high-temperature water specifically includes: placing the membrane electrode in water, heating and stirring, controlling the heating temperature at 30°C to 100°C, reducing the viscosity of the hydrophilic organic matter, dissolving it in the water, and leaching it during stirring or ultrasound.
[0043] Exemplarily, the removal of soluble organic matter by leaching the membrane electrode in a high-temperature alkali solution specifically includes: placing the membrane electrode in a heated 1% to 35% alkali solution tank for stirring or ultrasonication to remove leaching-removable organic matter and pore-forming non-hydrophilic substances that can be removed by hot alkali, thereby accelerating the leaching speed. The dissolution percentage is controlled by controlling the temperature and dissolution time, and the dissolution ratio is 50% to 90%.
[0044] Exemplarily, the removal of soluble organic matter by placing the membrane electrode in an enzyme for degradation specifically includes: placing the membrane electrode in a solution containing an organic matter decomposing enzyme, keeping it warm at 25 to 40°C for 1h to 72h, then taking it out and ultrasonicating it with clean water for 0.5h to 2h. In this way, the degradable organic matter on the membrane electrode is removed. The dissolution ratio is controlled at 50% to 90% by controlling the degradation time, temperature and enzyme type. It is determined whether most of the cellulose is dissolved by detecting the cellulose and cellulose decomposition products in the solution.
[0045] Preferably, the soluble organic matter includes one or more of cellulose, alginic acid, starch, and gum arabic, and the molecular weight is preferably 10,000-1,000,000.
[0046] In some embodiments, the organic matter can be formed into rod-shaped, spherical and other micelles to occupy the membrane electrode catalyst layer by adjusting the solution pH, temperature, solvent, organic molecular weight, etc. during the slurry preparation process, and the organic matter can be leached out to form pores through step 4), thereby increasing the porosity, forming nanometer-scale pores, and narrowing the pore size distribution. For example, the solution pH is adjusted to > 10, the temperature is between 30°C and 60°C, the organic molecular weight is between 10,000 and 200,000, and the formed micelles are controlled to be > 10nm. This is conducive to the formation of nanometer-scale pores during dissolution.
[0047] In some embodiments, the soluble salt includes one or more of ammonium bicarbonate, ammonium carbonate, and sodium carbonate.
[0048] In some embodiments, a slurry containing a soluble salt is coated on a substrate membrane, and when the slurry is not dry, the soluble salt is decomposed to release gas by heating (for example, placing the membrane electrode on a heating plate or in an oven) to form extremely small pores. Preferably, the amount of salt added, the temperature and the time are controlled to form a catalytic layer with a small pore size and a narrow pore distribution. For example, the amount of salt added is controlled to be less than 5% of the total slurry, the temperature is controlled at 30°C to 60°C, and the time is controlled at 2 to 15 minutes, and the proportion of nanoscale pores formed is >50%.
[0049] In some embodiments, the pore-forming non-hydrophilic material includes one or more of silicon-based materials such as glass fiber or metals that can be dissolved by alkali solution.
[0050] In some embodiments, the pore-forming non-hydrophilic substance plays a place-occupying role in the prepared membrane electrode. The membrane electrode is immersed in a hot alkaline solution or circulated to remove the pore-forming non-hydrophilic substance and form pores.
[0051] In some embodiments, the insoluble hydrophilic oxide includes one or more of zirconium oxide, titanium oxide, molybdenum oxide, etc. After removing other substances, the remaining insoluble hydrophilic oxide plays a hydrophilic role in the pores, transfers water to the catalyst, and improves the catalyst utilization rate.
[0052] In some embodiments, the added amount of the composite hydrophilic substance accounts for 1% to 20% of the total mass of the slurry.
[0053] Preferably, in the composite hydrophilic substance, the mass ratio of the soluble hydrophilic substance, the pore-forming non-hydrophilic substance and the insoluble hydrophilic oxide is in the range of 0.1-10%: 0.1-5%: 0.1-5%.
[0054] Preferably, the coating method in step 2) is spraying, scraping or slit coating, screen printing. The hydrophilicity of the alkaline electrolyzed water base film is not good, and the contact angle is generally greater than 90°. The present invention preferably pre-treats the base film: a mesh or dot hydrophilic organic layer is coated on the surface of the base film, but a continuous film is controlled not to be formed, and the thickness of the coating slurry layer is controlled to be 100nm to 1μm.
[0055] In some embodiments, step 3) drying and hot pressing specifically includes: placing the membrane electrode in an oven at 50-150°C for 1-8 hours; then hot pressing using a hot press at a temperature of 100-200°C, a pressure of 1-10 bar, and a hot pressing time of 1-30 minutes. Hot pressing makes the catalyst layer and the substrate layer more firmly bonded, reduces the interlayer gap caused by the leaching process, and reduces the contact resistance.
[0056] In some embodiments, the catalyst is Pt and Pt-based compounds and alloys, Ir and Ir-based compounds and alloys, Fe and Fe-based compounds and alloys, Ni and Ni-based compounds and alloys, and the binder is a fluoride resin binder, a polysulfone resin binder, a polyethersulfone resin binder, acrylonitrile and other alkali-resistant and high-temperature resistant binder. The type and amount of the catalyst and binder are selected with reference to the prior art and are not particularly limited.
[0057] The second aspect of the present invention provides a membrane electrode prepared by the above method.
[0058] The third aspect of the present invention provides an application of a membrane electrode prepared by the above method, which is used for producing hydrogen by alkaline water electrolysis.
[0059] The membrane electrode and its preparation method and application of the present invention are described in detail below through examples.
[0060] Example 1
[0061] A method for preparing a membrane electrode comprises the following steps:
[0062] 1) 100 g of Ni catalyst containing 1% (mass percentage) Pt, 30 g of solvent water, 20 g of n-propanol, 400 g of 5% perfluorosulfonic acid solution (binder) and a composite hydrophilic substance are mixed to obtain a hydrophilic slurry, wherein the composite hydrophilic substance includes 2 g of sodium carboxymethyl cellulose (molecular weight 50,000) + 2 g of glass fiber + 2 g of zirconium oxide;
[0063] 2) coating the hydrophilic slurry on a substrate membrane to obtain a uniformly coated membrane electrode;
[0064] 3) drying the membrane electrode at 80°C for 24 hours and hot pressing at a temperature of 120°C and a pressure of 20 bar for 10 minutes in a hot press;
[0065] 4) The membrane electrode treated in step 3) is placed in a 30% alkali solution tank at a temperature of 60°C and a concentration of 30% and ultrasonically stirred for 48 hours. The sodium carboxymethyl cellulose is dissolved in the high-temperature alkali solution or degraded into small molecules and leached out. The glass fiber is dissolved in the hot alkali to obtain a porous membrane electrode.
[0066] 5) The porous membrane electrode was cleaned with deionized water and then dried in an oven at 80°C for 2 hours.
[0067] Example 2
[0068] 1) Mix 100g of Ni catalyst containing 3% (mass percentage) Fe, 25g of solvent water, 25g of n-propanol, 400g of 60% PTFE binder solution and a composite hydrophilic substance to obtain an anode hydrophilic slurry. Mix 100g of Ni catalyst, 25g of solvent water, 25g of n-propanol, 400g of 60% PFSA binder solution and a composite hydrophilic substance to obtain a cathode hydrophilic slurry. The composite hydrophilic substance is 3g of hydroxypropyl methylcellulose (molecular weight 100,000) + 2g of zirconium oxide;
[0069] 2) coating the cathode hydrophilic slurry and the anode hydrophilic slurry on the substrate membrane respectively to obtain a uniformly coated membrane electrode;
[0070] 3) drying the membrane electrode at 80°C for 12 hours, and hot pressing at a temperature of 130°C and a pressure of 30 bar for 10 minutes in a hot press;
[0071] 4) The membrane electrode treated in step 3) is loaded into the battery stack, and the battery stack is not connected to electricity and enters liquid circulation operation. The liquid operating temperature is 60°C, the alkali solution concentration is 4%, the alkali solution circulation rate is 2L / min, and the alkali solution circulation time is 48 hours. The cellulose is in the high-temperature alkali solution so that the hydrophilic organic matter is dissolved or degraded into small molecules under alkaline conditions to obtain a porous membrane electrode.
[0072] 5) After the soluble substances are dissolved out, the fuel cell stack can be operated to produce hydrogen by electrolysis.
[0073] Example 3
[0074] 1) 100 g of 20% Pt / C catalyst, 100 g of solvent water, 200 g of 10% PFSA binder and composite hydrophilic substance (5 g of gum arabic + 2 g of zirconium oxide) were mixed to obtain cathode hydrophilic slurry. Catalyst (50 g of iridium oxide catalyst + 50 g of Ni catalyst), 100 g of solvent water, 200 g of 10% PFSA binder and composite hydrophilic substance (2 g of gum arabic + 2 g of zirconium oxide) were mixed to obtain anode hydrophilic slurry.
[0075] 2) coating the cathode hydrophilic slurry and the anode hydrophilic slurry on a substrate membrane to obtain a uniformly coated membrane electrode;
[0076] 3) Dry the membrane electrode at 80°C for 24 hours, and press it in a hot press at 120°C and 20 bar for 10 minutes;
[0077] 4) The membrane electrode treated in step 3) is placed in a liquid tank with an aqueous solution of arabic gum enzyme (50 mg / L) at a temperature of 40°C and ultrasonically stirred for 5 hours. Under the action of the high-temperature enzyme, the gum arabic is degraded into small sugar molecules that are leached to form pores to obtain a porous membrane electrode.
[0078] 5) The porous membrane electrode was cleaned with deionized water and then dried in an oven at 80°C for 2 hours.
[0079] Example 4
[0080] The difference from Example 1 is that before the hydrophilic slurry is coated on the basement membrane, the basement membrane is pretreated: a 300-mesh screen is covered on the basement membrane, and a 1% hydroxypropyl cellulose solution is sprayed on the screen surface by ultrasonic spraying, with a spraying thickness of 50 nm. Then the screen is removed, and the treated diaphragm is placed in a 60° C. oven for drying for 1 hour and then taken out for use. The remaining steps are the same as in Example 1.
[0081] Example 5
[0082] 100 g of nickel-iron catalyst, 50 g of solvent water, 400 g of 5% sulfonated polysulfone binder and composite hydrophilic material (3 g of ammonium bicarbonate + 2 g of zirconium oxide) were mixed to obtain a hydrophilic slurry;
[0083] The hydrophilic slurry is coated on the substrate membrane in a constant temperature and humidity room, the membrane electrode is dried at 80°C for 24 hours, and hot pressed at a temperature of 120°C and a pressure of 20 bar for 10 minutes in a hot press; the membrane electrode is heated at 45°C for 10 minutes, ammonium bicarbonate is decomposed into carbon dioxide and ammonia, and a uniformly coated porous membrane electrode is obtained during the gas overflow process. The remaining steps are the same as in Example 1.
[0084] Comparative Example 1
[0085] 1) 100 g of Ni catalyst containing 1% Pt, 30 g of solvent water, 20 g of n-propanol, and 400 g of 5% perfluorosulfonic acid binder were mixed to obtain an original slurry.
[0086] 2) coating the original slurry on a substrate membrane to obtain an original membrane electrode;
[0087] 3) The membrane electrode was dried at 80° C. for 5 hours, and hot pressed at a temperature of 140° C. and a pressure of 20 bar for 15 minutes.
[0088] The membrane electrodes prepared in the examples of the present invention and the comparative examples were subjected to performance tests, and specific data are shown in the table below.
[0089] Table 1
[0090]
[0091]
[0092] Table 2
[0093]
[0094] Table 3
[0095] Hydrophilicity-contact angle° Pre-treated basement membrane (Example 5) <90° Porous membrane electrode (Examples 1-5) <90° Original membrane electrode (Comparative Example 1) >130°
[0096] Table 4
[0097]
[0098]
[0099] The hydrophilic porous membrane electrode catalyst prepared in the embodiment of the present invention has a utilization rate increased by 20% and a membrane electrode impedance reduced by 25% compared with the original membrane electrode.
[0100] Obviously, the above embodiments of the present invention are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are within the spirit scope of the present invention.
Claims
1. A method for preparing a membrane electrode, characterized in that: The steps include: 1) mixing a catalyst, a binder and a composite hydrophilic substance to obtain a hydrophilic slurry, wherein the composite hydrophilic substance comprises one or more of a soluble hydrophilic substance, a pore-forming non-hydrophilic substance, and an insoluble hydrophilic oxide; 2) coating a mesh or dot-shaped hydrophilic organic layer on the surface of the base film, and then coating the hydrophilic slurry on the base film to obtain a uniformly coated membrane electrode; 3) drying and hot pressing the membrane electrode; 4) removing the soluble hydrophilic substances and / or pore-forming non-hydrophilic substances in the membrane electrode to obtain a porous hydrophilic membrane electrode; The soluble hydrophilic substance includes one or more of soluble organic matter and soluble salt; The pore-forming non-hydrophilic substance includes one or more of silicon-based substances or metals that can be dissolved by alkali solution; The insoluble hydrophilic oxide includes one or more of zirconium oxide, titanium oxide, and molybdenum oxide.
2. The preparation method according to claim 1, characterized in that: In step 4), soluble organic matter is removed by placing the membrane electrode in an operating alkaline electrolysis stack, or by leaching the membrane electrode in alkaline solution, high-temperature alkaline solution or high-temperature water, or by degrading the membrane electrode in an organic solvent or enzyme to remove soluble organic matter.
3. The preparation method according to claim 2, characterized in that: The soluble organic matter includes one or more of cellulose, alginic acid, starch, and gum arabic.
4. The preparation method according to claim 3, characterized in that: The molecular weight of the soluble organic matter is 10,000 to 1,000,000.
5. The preparation method according to claim 1, characterized in that: The soluble salt includes one or more of ammonium bicarbonate, ammonium carbonate, and sodium carbonate.
6. The preparation method according to claim 5, characterized in that: A hydrophilic slurry containing soluble salts is coated on a substrate membrane, and when the slurry is not dry, the soluble salts are decomposed by heating to release gas, thereby forming pores.
7. The preparation method according to claim 6, characterized in that: In step 4), the membrane electrode is immersed in hot alkaline solution or circulated to remove the pore-forming non-hydrophilic substances and form pores.
8. The preparation method according to claim 7, characterized in that: The addition amount of the composite hydrophilic substance accounts for 0.1% to 20% of the total mass of the slurry; In the composite hydrophilic substance, the mass ratio of the soluble hydrophilic substance, the pore-forming non-hydrophilic substance and the insoluble hydrophilic oxide is in the range of 0.1-10%: 0.1-5%: 0.1-5%.
9. The preparation method according to claim 1, characterized in that: The coating method in step 2) is spraying, blade coating, slit coating or screen printing; The hydrophilic organic matter includes one or more of cellulose, alginic acid, starch, and gum arabic.
10. The preparation method according to claim 9, characterized in that: The molecular weight of hydrophilic organic matter is 10,000 to 1,000,000.
11. A membrane electrode prepared by the method according to any one of claims 1 to 10.
12. A use of a membrane electrode prepared by the method according to any one of claims 1 to 10 or a membrane electrode according to claim 11, wherein the membrane electrode is used for producing hydrogen by alkaline water electrolysis.
Citation Information
Patent Citations
Porous gas diffusion layer and preparation method thereof
CN104779399A
Composite diaphragm with super-hydrophilic surface and integral cross-linked structure for hydrogen production by alkaline water electrolysis and preparation method of composite diaphragm
CN117512693A